Questionify: Gamification in Education - Kasinathan, Vinothini; Mustapha, Aida; Fauzi, Rahmat; Che Abdul Rani, Mohamad Firdaus (International Journal of Integrated Engineering, 2018)
In the education industry, lecturers are finding ways to improve students’ concentrations and grades by using smart devices to track students’ assignment or tutorial progress. One of the few possible and attractive solution is by using the gamification technique. This paper proposes an educational application called Questionify that implements the gamification elements and allow users to collect points, gain achievements, increase motivation and engagement towards students’ coursework in Software Engineering subject. Questionify is developed using C# and Java language has been evaluated using questionnaire among 24 respondents. The findings showed that the respondents believe that gamification can do better in education as compare to the traditional method of teaching the students. In the future, this gamification approach will be tested on more technical subjects such as programming and networking subjects to help students engage in a different learning approach.